Pollution of Beach Sand From Selected Recreational Reservoirs by Microplastics - Popenda, Agnieszka; Wiśniowska, Ewa (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The presence of microplastics have been ubiquitously confirmed in aquatic environment possessing the potential risk to the health of ecosystem. Most studies concerning microplastics are focused on water bodies, but it is considered that sediments and sands from the beaches may to be a long-term sink for microplastics. High concentrations of microplastics have been found in sand beach in Europe and all over the world.
Keywords: microplastics; sand beaches; contamination; recreational reservoirs; micropollutants; mikroplastik; plaża; zanieczyszczenia; zbiornik rekreacyjny; mikrozanieczyszczenia